KEPADATAN DAN DISTRIBUSI KEONG MAS (Pomacea canaliculata) DI SALURAN IRIGASI BENDUNGAN BATANG SAMO DESA SUKA MAJU KABUPATEN ROKAN HULU - -, Rozakiyah; Yolanda, Rofiza; Purnama, Arief Anthonius (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
Study about density and distribution pattern of golden snail (Pomacea canaliculata) at irigation Batang Samo Suka Maju Village Rokan Hulu Regency has been conducted in August to December 2014 with survey method and purposiv random sampling tecniques by used 1x1 meters squared plot and thrown at three observation stations as much as 50 hurl times. The results shown that density P.canaliculata subsequently in three station is 12,72 individuals/m2 in station 1, followed 4,92 individuals/m2 in station 2 and followed 8,4 individuals /m2 in station 3. Distribution pattern of P. canaliculata in three observation was grouped.